Building a Media Literate Society: Pathways to Improve Media and Information Literacy Education in Pakistan. (December 2022) - Jamil, Sadia; Iqbal, Azhar; Ittefaq, Muhammad; Kamboh, Shafiq Ahmad
This mixed-method study investigates the state of media and information literacy education in Pakistan by underlining the availability of relevant courses and trained teaching and research faculty at both public and private universities. Using United Nations Educational, Scientific and Cultural Organization's (UNESCO) framework, this study explores the perception of faculty members across six key areas of general education and teacher development to improve the quality of media and information literacy in the country. These six key areas include (a) policy and vision, (b) curriculum and assessment, (c) pedagogy, (d) media and information, (e) organization and administration, and (f) teachers' professional development.